A new dynamic seven-stage model for thickness prediction of the film between valve plate and cylinder block in axial piston pumps. (September 2016) - Zhang, Chao; Huang, Shaokang; Du, Jun; Wang, Xingjian; Wang, Shaoping; Zhang, Haiyan
Axial piston pumps are very important to the hydraulic system on aircrafts, and their reliability plays critical role for ensuring the reliability and safety of aircrafts. The thickness prediction of the film between valve plate and cylinder block has received considerable concerns. This article presents a new dynamic seven-stage model for the thickness prediction of the film between valve plate and cylinder block in axial piston pumps. By dividing the rotation of the cylinder into seven stages, the complete analytical expression of the pressure distributions between valve plate and cylinder block is derived. The lubrication film forces and torques exerted on the cylinder block are then calculated and the film is determined by analyzing the complex dynamics of cylinder block. Experiments have been conducted and the results show that the proposed model is effective.